MOLP: Learning math through online learning portal - Fakhrunrozi, Nur Ain Najla; Zahiyan, Irdina Nurain; Zamri, Nur Athirah; Wan Mohammad, Wan Anisha; Kechil, Rafizah (2022)
The Covid-19 pandemic has tremendously changed our daily routine especially in the education field. Open distance learning or ODL was implemented as another alternative for students and educators to continue the teaching and learning process as they did not get to meet physically. Many platforms have been used by educators to deliver teaching and learning materials to students. This enables students to access learning material anywhere, at any time. However, most of the materials are scattered everywhere. There is no one platform that students can use to access all the materials easily and interactively at the same time. Thus, MOLP: Learning Math through Online Learning Portal was developed as a one-stop centre to combine all the interactive materials together. At the same time, since it is developed by students themselves, MOLP can provide another way of revision where students do not only use MOLP in their studies, but MOLP developers can enhance their knowledge on the course when they develop the content. MOLP was specifically developed for Pre-Commerce students who are learning Intensive Mathematics 1. A survey has been conducted to understand the student's limitations with the distribution of the current learning materials and their satisfaction in using MOLP. All the respondents agreed that MOLP can help them in their studies and they fully recommended MOLP to their friends.